Analysing Coverage of Maternal Mental Health in Indian Newspapers: A Content Analysis - Dixit, Prabhat; Pandey, Hemant Kumar; Sharma, Sunil (Indian Journal of Community Health, 2024)
Issues related to maternal mental health, such as anxiety, depression, and psychosis both during and after pregnancy, have attracted international attention. The World Health Organization has documented a notable occurrence, particularly in developing nations. The function of print media in raising awareness about these concerns is vital. This study investigates the extent to which Jaipur's daily newspapers in 2022 address the topic of maternal mental health. The objective is to evaluate how often this issue is covered and the influence it has on women's knowledge and understanding. A descriptive survey study methodology was employed to collect data from 250 women. The data collection process involved purposive sampling and the use of questionnaires. An examination of the content of Rajasthan Patrika and Dainik Bhaskar in July 2022 found that there was no reporting or discussion on maternal mental health. According to surveys, 35% of the participants reported experiencing mental difficulties when they were pregnant, although a majority of 84% did not actively seek medical assistance. Many respondents (90%) expressed the opinion that newspapers should publish articles on this subject. The study finds that there is a notable disparity in media coverage of maternal mental health in Jaipur, indicating a requirement for heightened awareness and focused health communication initiatives.